The Wiley handbook of global workplace learning - Kenon, Vanessa Hammler; Palsole, Sunay Vasant (Wiley handbooks in education., 2019)
The Wiley Handbook of Global Workplace Learning explores the field of workplace education using contributions from both experts and emerging scholars in industry and academia. Unlike many previously published titles on the subject, the Handbook focuses on offering readers a truly global overview of workplace learning at a price point that makes it accessible for independent researchers and Human Resources professionals. Designed to strike a balance between theory and practice, the Handbook provides a wealth of information on foundational topics, theoretical frameworks, current and emerging trends, technological updates, implementation strategies, and research methodologies. Chapters covering recent research illustrate the importance of workplace learning topics ranging from meditation to change management, while others give pragmatic and replicable applications for the design, promotion, and implementation of impactful learning opportunities for employees at any company, regardless of industry.